EDUCATIONAL SERVICE QUALITY FOR MADRASAH BRANDING: SERVQUAL ANALYSIS IN PRIVATE ISLAMIC SCHOOLS - Muaz Muaz; Arip Amin; Novianti Azizah Rahman (JURNAL EDUSCIENCE, 2026)
Purpose – This study investigates the role of educational service quality in shaping madrasah branding through five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy, within the context of private Islamic junior secondary schools.Methodology – A qualitative multisite approach framed the investigation across two private madrasahs in Majalengka. Empirical data were obtained through in-depth interviews involving principals, teachers, students, parents, and community representatives, supported by participatory observation and institutional documentation. Data were interpreted through an interactive analytical process consisting of reduction, categorization, and conclusion development.Findings – Tangibles influence first impressions through physical facilities and institutional visibility. Reliability strengthened public confidence through stable academic practices and consistent instructional delivery. Responsiveness enabled the schools to adapt their educational services to changing social and pedagogical demands. Assurance contributed to institutional credibility through both formal recognition and social trust, while empathy emerged as the strongest element in sustaining emotional attachment among students and parents. Service experience across these dimensions played a greater role in shaping institutional reputation than promotional activities alone.Contribution – The study proposes a conceptual pattern in which service quality develops into trust, forms institutional image, and gradually strengthens branding. This perspective extends SERVQUAL beyond service evaluation and positions it as a strategic framework for institutional reputation development in Islamic educational management.